2011
DOI: 10.1002/mrd.21286
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gene expression pattern of bovine blastocysts at three stages of development

Abstract: Blastocyst formation is a primordial event of pre-implantation development since it is required for pregnancy establishment and progression. The blastocyst plays a pivotal role because it is the stage at which the embryo starts coordinated cross-talk with the mother. It is also the terminal step before transfer in bovine; it reflects all stresses the embryo may have faced during the process of in vitro treatment. Achieving the formation of a morphologically healthy blastocyst following normal kinetics is good,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 79 publications
2
26
0
Order By: Relevance
“…The expression patterns of OCT4, IFN , and CDX2 during early embryonic development allow assessment of the quality of blastocysts produced (Bauer et al, 2010;Ross et al, 2007). In ruminant, the function of IFN is the recognition of pregnancy (Bazer et al, 2008) and IFN gene expression is higher in hatched blastocysts than in expanded and early embryos (Rekik et al, 2011). This is consistent with increased IFN production in cattle blastocysts and conceptuses when elongation commences (Ealy et al, 2001).…”
Section: Discussionmentioning
confidence: 55%
“…The expression patterns of OCT4, IFN , and CDX2 during early embryonic development allow assessment of the quality of blastocysts produced (Bauer et al, 2010;Ross et al, 2007). In ruminant, the function of IFN is the recognition of pregnancy (Bazer et al, 2008) and IFN gene expression is higher in hatched blastocysts than in expanded and early embryos (Rekik et al, 2011). This is consistent with increased IFN production in cattle blastocysts and conceptuses when elongation commences (Ealy et al, 2001).…”
Section: Discussionmentioning
confidence: 55%
“…Because there was no significant difference in developmental stage or embryo quality grade according to morphological evaluation of all groups on Day 8, the increased cell number of the developing embryos after insulin treatment may not be linked to a more progressed developmental stage, but rather implies increased proliferation. This observation was confirmed by transcriptome analyses, because none of the DETs in the INS10 or INS0.1 groups is common with those known to be associated with stage-related differences (Rekik et al 2011). An increased cell number more likely indicates accelerated proliferation and growth within the equally developed groups, because embryo stage as a confounder can be excluded.…”
Section: Discussionmentioning
confidence: 68%
“…PLAC8 expression has been reported in many species, such as zebrafish (3), mice (1), bovines (4)(5)(6)(7)(8)(9), and rabbits (16). However, little is known regarding PLAC8 expression in human oocytes and embryos.…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest that PLAC8 plays a crucial role in normal embryo development (3). In the evaluation of bovine embryo quality, PLAC8 is a biomarker that is used to predict pregnancy outcome (4)(5)(6)(7)(8)(9). Two recent reports investigated bovine embryos derived in vitro (4) and in vivo (10), and they demonstrated that PLAC8 was highly expressed in cells from embryos that were capable of developing into calves.…”
mentioning
confidence: 93%